ANALISIS WARNA McDONALD’S DAN PERBEDAAN KESETIAAN PELANGGAN (Studi Tentang Warna Logo McDonald’s dan Kesetiaan Pelanggan dari Orang Manado, Tionghoa dan Batak) - Michael Jibrael Rorong (SEMIOTIKA: Jurnal Komunikasi, 2016)
The fields of science communication studies provide a major role in the communication process. Communication is able to be applied in any field of science and in any contexts, even in social, technology and business. In business world, communication has a role in creating a different view on the subjective view, by utilizing the communication studies about purposes which communication theories of symbols can be utilized. Communication theories about symbol refers to the semiotic theory which in this study the author uses semiotic theory of communication by Charles Saunders Pierce for framing author’s research, which entitled as The Analysis of Differences In McDonald Restaurant’s Customer Loyalty With Descriptive Study Towards The Differences In Customer Perception To The Attractiveness Of The McDonald's Logo Which Combined With Red And Yellow Colors Based On Manado, Batak and Tionghoa People And Knowledge. The author uses the constructivist paradigm (interpretive) and qualitative research method.Keywords: Perception, Customer Loyalty, Semiotics, Colour, Ethnicity, Constructivist